Логістичне управління енергетичними потоками: теоретико-методологічні засади - Перебийніс, В.І.; Рогоза, М.Є.; Миколенко, І.Г.; Кононенко, Ж.А. (Економічний вісник Донбасу, 2023)
Уточнено теоретико-методологічні засади формування логістичного управління енергетичними потоками. Отримало подальший розвиток тлумачення економічні поняття «енергетичний потік», «розмірність енергетичного потоку». Розглянута сутність (субстанція) енергетичного потоку. Обґрунтовані стадії руху енергетичного потоку: стадія закупівель, стадія зберігання, стадія використання (трансформації). Сформульовано поняття «логістичне управління енергетичними потоками». Здійснено розробку матриці логістичного управління енергетичними потоками у процесі енергопостачання (енергогенерації) та енергоспоживання. Обґрунтовано завдання оптимізації енергетичних потоків. The article describes theoretical and methodological principles of logistic management of energy flows. It is appropriate to consider the energy flow as a set of energy resources circulating in the logistics system, as well as between the logistics system and its external environment in order to provide energy for logistics processes. A part of the energy flow is a component of the material flow. This applies, in particular, to energy resources that have a liquid, solid and gaseous material substance. Dimensionality of the energy flow can be expressed as the ratio of the amount of energy (in conventional units of fuel) to the unit of measurement of time (hour, day, month, quarter, year). The energy flow turns into a stock of energy resources if it is considered during the implementation of logistics operations at a certain point in time (except for electricity, which is quite difficult to accumulate in many types of economic activity). It has been established that the energy flow goes through the following stages: procurement stage, storage stage and use (transformation) stage. Approaches to calculating the amount of energy flow at the specified stages and the total amount of energy flow have been reasoned. The logistics management of energy flows should be understood as the process of strategizing, planning and controlling the flow of energy resources from the supplier to the business entity (as a logistics system), as well as in the intra-production logistics subsystem during energy use. The matrix of the logistic management system of energy flows in the process of energy supply (energy generation) and energy consumption has been developed. It is appropriate to consider the task of optimizing energy flows as minimization of the total logistics costs of business entities and territorial communities in the process of energy supply and energy use.